2019
DOI: 10.1002/ep.13220
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis of parabolic trough concentration photovoltaic/thermal system for using in buildings

Abstract: In this research, a parabolic trough concentrating photovoltaic thermal (CPVT) was used to provide the energy needed for a residential building. In order to do this, the required amount of heating and cooling and electrical energy was first obtained using Carrier software, then the electrical demand was obtained according to the standard model and governing relations. In the next step, the CPVT as a source of heat and cooling, and electrical energy for the building, was simulated in TRNSYS software. In order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In addition, TRNSYS also has open‐source code facility in which the pre‐existing models can be modified and validated for optimization and the results obtained from TRNSYS have proved to be reliable and are in good agreement with the experimental results within an error percentage of about 5–10% 10 . Thus, it is convenient modular system approach contributes to wider adaptability for detailed analysis of individual system components and their effect on overall system performance for a variety of applications that include solar power plants, 11 building heating, 12 hybrid systems, 13 desalination, 14 energy storage, 15 heating, ventilation and air conditioning (HVAC), 16 and SWH, 17‐26 respectively.…”
Section: Introductionmentioning
confidence: 73%
“…In addition, TRNSYS also has open‐source code facility in which the pre‐existing models can be modified and validated for optimization and the results obtained from TRNSYS have proved to be reliable and are in good agreement with the experimental results within an error percentage of about 5–10% 10 . Thus, it is convenient modular system approach contributes to wider adaptability for detailed analysis of individual system components and their effect on overall system performance for a variety of applications that include solar power plants, 11 building heating, 12 hybrid systems, 13 desalination, 14 energy storage, 15 heating, ventilation and air conditioning (HVAC), 16 and SWH, 17‐26 respectively.…”
Section: Introductionmentioning
confidence: 73%
“…Due to the need to use clean energy sources, the use of renewable is increasing over the years [1][2][3]. Previous works have shown that the integration of RE, such as solar PV, the small hydro, wind, geothermal, and hydrogen, will reduce greenhouse gasses such as CO2.…”
Section: Introductionmentioning
confidence: 99%
“…These systems focus the sunlight on a focal area which allows the system (photovoltaic cell and absorber) to produce electrical and thermal energies . CPVT is a photovoltaic technology that generates electricity from sunlight . Unlike conventional photovoltaic systems, it uses lenses or curved mirrors to focus sunlight onto small, highly efficient, multi‐junction (MJ) solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] CPVT is a photovoltaic technology that generates electricity from sunlight. 4 Unlike conventional photovoltaic systems, it uses lenses or curved mirrors to focus sunlight onto small, highly efficient, multi-junction (MJ) solar cells. In addition, CPV systems often use solar trackers and sometimes a cooling system to further increase their efficiency.…”
Section: Introductionmentioning
confidence: 99%